Optimizing Bacterial Cellulose from Coffee Husk Waste for Enhanced Vegan Leather Production - Wahyudi, Aleyda Nur Halizah; Ardyati, Tri; Srihardyastutie, Arie; Habibi, Ananta Naufal; Kato, Masashi (The Journal of Experimental Life Science, 2026)
Coffee production in Indonesia continues to increase each year, necessitating sustainable waste management to reduce the accumulation of coffee husk waste in the environment. This waste still contains natural carbon sources that can potentially be utilized as a fermentation medium for bacterial cellulose (BC) production, which is promising for vegan leather applications. This study aims to determine the most effective combination of molasses and ammonium sulfate (ZA) to enhance BC production and optimize the BC pretreatment process for vegan leather application. In this study, chemical composition analysis was also carried out using Fourier transform infrared (FTIR) spectroscopy analysis on samples of coffee fruit peel following the thermal delignification process to determine the optimal conditions for the process. BC production was carried out over 14 days with treatment variations of 5%, 10%, and 15% molasses and 0.3%, 0.5%, and 1% ZA. The pretreatment involved pressing and coating with a coconut oil–beeswax mixture, followed by characterization of BC through physicochemical properties, weight, and thickness. The effect of varying concentrations of molasses and ZA in the coffee husk extract medium had an effect on the weight and thickness of the cellulose membrane produced, with optimal results in treatment P3 (10% molasses and 0.3% ZA) (weight 509 g; thickness 9.69 mm). The pH value was measured before and after fermentation and showed a decrease caused by the activity of acetic acid bacteria.